Career Education: Concluding Remarks. (December 2019) - Cinamon, Rachel Gali; Flum, Hanoch; Hardin, Erin E.
The interventions presented in the current special issue have the potential to decrease social and economic gaps. At the same time, several important aspects that are central to the rapid changes in education and in the world of work were not included or given minimal attention in these interventions. In this concluding article, we reflect upon these issues in the hope that future studies and career education work will focus and elaborate upon theme.